2019
DOI: 10.1002/anie.201913088
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Tandem Routes for the Copolymerization of Ethylene with Polar Functionalized Internal Olefins

Abstract: Transition metal catalyzed ethylene copolymerization with polar monomers is a highly challenging reaction. After decades of research, the scope of suitable comonomer substrates has expanded from special to fundamental polar monomers and, recently, to 1,1‐disubstituted ethylenes. Described in this contribution is a direct and tandem strategy to realize ethylene copolymerization with various 1,2‐disubstituted ethylenes. The direct route is sensitive to sterics of both the comonomers and the catalyst. In the tand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(44 citation statements)
references
References 61 publications
0
44
0
Order By: Relevance
“…In the field of polyolefin research [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], many studies have reported on the homopolymerization of ethylene [ 21 , 22 , 23 , 24 ], different higher 1-alkene [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ], and linear internal alkenes [ 32 , 33 , 34 ] using Brookhart-type α-diimine nickel and palladium catalysts [ 35 , 36 , 37 , 38 , 39 , 40 , 41 ] because of the chain-walking process [ 42 , 43 , 44 , 45 ]. The interest in highly branched polyolefins such as dendrimer and hyper branched polymers has increased obviously in recent years owing to these unique physical properties, chemical properties, and their potential applications as adhesives, lubricants, and paints [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the field of polyolefin research [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], many studies have reported on the homopolymerization of ethylene [ 21 , 22 , 23 , 24 ], different higher 1-alkene [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ], and linear internal alkenes [ 32 , 33 , 34 ] using Brookhart-type α-diimine nickel and palladium catalysts [ 35 , 36 , 37 , 38 , 39 , 40 , 41 ] because of the chain-walking process [ 42 , 43 , 44 , 45 ]. The interest in highly branched polyolefins such as dendrimer and hyper branched polymers has increased obviously in recent years owing to these unique physical properties, chemical properties, and their potential applications as adhesives, lubricants, and paints [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the Chen group developed a phosphine sulfonate palladium catalyzed ethylene copolymerization with 1,2‐disubstituted polar olefins (Scheme 5a). [ 7 ] Various types of 1,2‐disubstituted polar olefins could be successfully incorporated by this method to construct polar functionalized polyethylenes with functionalities such as ether, ketone, and ester groups. Notably, this method is able to incorporate 1,2‐difunctionalized alkenes into the polyethylene chain and locate two functional groups at the adjacent positions.…”
Section: Recent Advancesmentioning
confidence: 99%
“…This interest is due to their outstanding behaviour in polymerization of olefins for production of linear to hyperbranched and low to high molecular weight (M w ) polyolefins, introduction of polar and even bio-sourced comonomers into the backbone of polyolefins. [24][25][26][27][28][29][30][31][32] Based on this, there are many papers on the study of these catalysts behaviour. Moreover, they kept their position in the mentioned systems for production of olefinic copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…Although the catalysts based on rare‐earth metals have shown good results in these kinds of polymerizations but transition metals especially the late ones are much more interesting and attractive. This interest is due to their outstanding behaviour in polymerization of olefins for production of linear to hyperbranched and low to high molecular weight (M w ) polyolefins, introduction of polar and even bio‐sourced comonomers into the backbone of polyolefins [24–32] . Based on this, there are many papers on the study of these catalysts behaviour.…”
Section: Introductionmentioning
confidence: 99%